Progressing haemolysis, elevated liver enzymes, low platelet count syndrome: near miss case - Verma, Urvashi; Agarwal, Shruti; Sahu, Sangita; Chahar, Ajit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
A 25 years old women presented in labour room with 30 weeks’ pregnancy in labour with breech with previous two caesarean section and scar tenderness with foetal bradycardia (FHR 90) and jaundice. After caesarean section in emergency hour she started bleeding in abdominal drain while uterus was well contracted. On investigation and examination diagnosed as HELLP syndrome, managed promptly by medical teams of three departments (obstetrician, anaesthesia and medicine).